Numerical study for the effect of angle between inner wall of Wehnelt electrode and its axis on beam dynamics in a thermionic electron gun - Hanyu Gao; Guoquan Ding; Xin Zhou; Dongbo Chang; Ying Tian; Mengxiang Dang (AIP Advances)
Welding electron guns are usually designed using the theory of electron optics, where a change in the size of the Wehnelt electrode in the electrostatic field causes variations in the motion behavior of the electron beam. In this study, the COMSOL software is used to carry out finite element simulations; under temperature-limited emission conditions, the influence of changing α, which is the angle between the inner wall of the Wehnelt electrode and its central axis, on the beam is mainly analyzed. The results indicate that a change in α causes a variation in the potential on the axis and its first and second derivatives to the axial distance, which in turn causes changes in the beam current and emittance and the radius and position of the beam waist; however, it has no significant effect on the kinetic energy of the electrons. When 75° < α ≤ 90°, the beam cannot be focused effectively. When 0° ≤ α ≤ 15°, the beam current is significantly reduced, and the Wehnelt electrode is most likely to be damaged. After synthetically analyzing the main characteristic parameters of the beam waist, when α = 60°, the requirements for focusing the electron beam of the electron gun in this study can be met.